The construction of national identity in Shakespeare’s King Lear and its filmic adaptation by Peter Brook - Antônio João Teixeira (Ilha do Desterro, 2006)
The national consciousness that had begun in the reign of Queen Elizabeth I—due to the enmity that England had with France, the Reformation, and the flourishing of national literature—strengthened with the reign of James I, when the possibility of a unified Britain appeared. The displacement of characters in Shakespeare’s King Lear, whose first performance took place at the court of King James I, and the relevance of Dover, the place where the French invaders disembark, relate to the question of the definition of boundaries and the formation of a national identity in Jacobean England. In Peter Brook’s 1970 filmic adaptation of the play, the construction of this identity is metaphorized in the way the film reproduces the barbaric world of Lear in the mise-en-scène— practically bare sets, no music, rough cloth costumes, and wintry landscapes—and relates it to modern-day England in the art-house style of the film and its emulation of a sophisticated form of drama. Thus, the violent deeds of Lear’s reign, enhanced in the film, could, due to the characteristic style of art-films of the seventies, address the plights of a nation which can no longer rely on its status as the ruler of the world.